On Being “Anti-Sublimed”: Early Tales of Fear and Glory at Niagara Falls - Revie, Linda (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2009)
AbstractThis essay reads accounts of travel to Niagara from the 1790s-1840s through thelens of the sublime and the picturesque. Beginning with masculine adventurers whohave special claims to the Burkean sublime, and moving onto later male and femaletravellers who master their feelings of weakness and irrationality through a moreKantian-based approach to reasoning, the essay ultimately isolates the criticalstage in sublime logic when incomprehension diverts to meaning and presents thisbreaking through as a discursive strategy the author calls "the anti-sublime."